Odpowiedź:
zad 1
a) 2 1/3 + 6 2/3 = 8 3/3 = 9
b) 6 3/5 - 8 4/5 = - 2 1/5
c) 1 1/2 + 1/3 = 1 3/6 + 2/6 = 1 5/6
d) 5 2/3 + 1/2 = 5 4/6 + 3/6 = 5 7/6 = 6 1/6
e) 2 3/4 - 4 1/2 = 2 3/4 - 4 2/4 = 2 3/4 - 3 6/4 = - 1 3/4
f) 5 1/4 - 4 2/3 = 5 3/12 - 4 8/12 = 4 15/12 - 4 8/12 = 7/12
g) (2/3 * 4/9) : 1/3 = 8/27 * 3 = 8/9
h) (5/8 * 15/4) : 6/5 = 75/32 * 5/6 = 25/32 * 5/2 = 125/64 = 1 61/64
i) ( 1/2 * 1/3) : 1/6 = 1/6 * 6 = 1
j) (2/3 * 5/6) : 8/15 = (1/3 * 5/3) * 15/8 = 5/9 * 15/8 = 5/3 * 5/8 = 25/24 = 1 1/24
k) (1 2/3 : 8 4/7) * 6/7 = ( 5/3 : 60/7) * 6/7 = (5/3 * 7/60) * 6/7 = (1/3 * 7/12) * 6/7 =
= 7/36 * 6/7 = 1/6 * 1 = 1/6
l) ( 2 6/7 : 1 3/7) * 1/2 = ( 20/7 : 10/7) * 1/2 = ( 20/7 * 7/10) * 1/2 = 2 * 1 * 1/2 = 1